Investigation of Terminalia arjuna as potential IL-4 and IL-13 modulator for the prevention of autoimmune diabetes: A Pharmacoinformatics-based study: DOI: 10.48129/kjs.17337 - Unnisa, Aziz; Saheem Ahmad; Jandrajupalli, Suresh Babu; Younes, Kareem M.; Abobaker, Sally Hassan; Chandolu, Swarnalatha; Mohammad Khalid; Lakshmi Sudeepthi N (Kuwait Journal of Science, 2023)
Cytokines are proteins that play a critical role in the development, maturation, and functional activities of immune cells. For the first time, we have investigated the potential role of Terminalia arjuna as IL-4 and IL-13 modulators for preventing T1DM, i.e., autoimmune diabetes. It has been well documented that the stimulation of IL-4 and IL-13 can regulate the level of type 2 cytokines which can be maintained with the level of type 1 cytokines. In the present study, gallic acid, arjunolic acid, luteolin, ellagic acid, and arjunone were investigated for their potential modulating activity of IL-4 and IL-13. The active amino acid residues identified for IL-4 are VAL51, HIS58, ASP87, THR30, GLN54, THR63, ARG64, LYS84, and GLU60. The active amino acid residues identified for IL-13 are H: GLU46, H: TRP47, H: GLN61, L: PHE98, L: VAL97, L: GLU162, L: THR163, H: ARG105, L: GLN38, L: ASP85, H: GLY42, L: GLY41, H: PRO41, H: TRP47, and L: PHE98. The phytoconstituents demonstrated better modulating activity towards IL-13 than IL-4. Luteolin displayed better potential for both IL-4 and IL-13, and therefore we concluded that it could be used to modulate the activity of IL-4 and IL-13 for the prevention of autoimmune diabetes.